An Evaluation of Reporting Guidelines and Clinical Trial Registry Requirements Among Plastic Surgery Journals. Issue 2 (August 2018) - Checketts, Jake X.; Cook, Courtney; Imani, Saba; Duckett, Laurie; Vassar, Matt
Abstract : Background: Ensuring that published studies are of the highest methodological quality is a critical step in plastic surgery's transition to a more evidence-based field. Reporting guidelines and reporting of clinical trial registration may serve as promising avenues of increasing the methodological quality in plastic surgery trials. Objective: The objective of this study is to evaluate the rate at which plastic surgery journals require reporting guidelines, as well as the effect these policies have on adherence to reporting guidelines. Methods: Using journal's "Instructions for Authors, " we conducted a cross-sectional survey to evaluate journal policies regarding adherence to reporting guidelines and trial registration. We also examined whether trials published in journals referencing Consolidated Standards of Reporting of Trials (CONSORT) had higher rates of compliance with publishing a CONSORT flow diagram and whether journals with trial registration policies were more likely to contain registered trials than journals without these requirements. Results: Of the 20 plastic surgery journals, 13 (65%) did not mention a single guideline within their instructions to authors. Furthermore, 10 (50%) did not mention policies regarding clinical trial registration. In addition, journals with policies regarding the CONSORT statement were more likely to publish trials with a CONSORT flow diagram, and journals with policies regarding clinical trial registry were more likely to publish trials reporting registration. Conclusion and Relevance: Our study found that few plastic surgery journals mention reporting guidelines or trial registration in their instructions for authors. Our study also found that journal policies regarding guideline adherence and trial registration seem to be effective mechanisms toward improvement, and plastic surgery journals should consider adopting such policies.